Aesthetic hegemony of the new order: A critical review of cultural politics in Indonesia (1966-1998) - Novianto, Wahyu; Guntur, Guntur; Faruk, Faruk; Simatupang, Lono (International Journal of Visual and Performing Arts, 2024)
This research studies the aesthetic hegemony of the New Order in Indonesia. Thus far, the understanding has been that aesthetic matters are not related to the capital and feudal assets that construct them. To the contrary, this research analyzes how these two assets played a strategic role in establishing the aesthetic hegemony of the New Order. The research is conducted in the qualitative tradition, through a content analysis with a critical paradigm perspective. The data include documents in the form of literature, government policies, and the results of interviews. The results show that the United States of America, through the Ford Foundation, played an active role and contributed significantly to the establishment of aesthetic hegemony in the New Order. The United States was an agent that provided scholarships for art academics, young scientists, and artists to study art and philosophy in America and Europe. The style of abstract expressionism and the philosophy of absurdism were developed in Indonesia as a result of the active role of the United States of America. On the other hand, the New Order also built cultural centers on a central and regional level, including cultural parks and arts councils that were used as tools of cooptation. Through the function of â€œmentoring and developmentâ€, the role of cultural parks was to control the aesthetic activities of Indonesian citizens to suit the tastes of the ruler. The research results show that the aesthetic hegemony of the New Order had a double face, one with a character of modernism based on Western aesthetics, and the other with a noble adiluhung character of traditionalism based on traditional art.